The Effect of Compensation and Work Discipline on the Performance of the State Civil Apparatus in the Office Barru District Center For Statistics - Aigistina, Erni Salijah, Sirnan (Institute for Research and Community Service, 2021)
The objectives of this study are (1) to determine the effect of compensation on the performance of the state civil apparatus at the Central Bureau of Statistics of Barru Regency. (2) to determine the effect of work discipline on the performance of the state civil apparatus at the Central Bureau of Statistics of Barru Regency. (3) to determine the effect of compensation and work discipline together on the performance of the state civil apparatus at the Central Bureau of Statistics of Barru Regency. Data collection techniques in this study are the method of observation, interviews, and literature study. In this study, the population is the entire State Civil Apparatus (SCA) of the Central Statistics Agency office, totaling 32 people. In order for this study to provide generalizations with a very small error rate, and considering that the population is only 32 people, this research uses a sampling technique, namely saturated sampling (census). Thus the number of samples in this study were 32 people. The results of the study show that (1) Compensation partially affects the performance of the state civil apparatus at the Barru Central Bureau of Statistics. Where the results obtained by compensation have a tcount value of 6.121 > ttable. 1.6973 and the significance level of t is less than 0.05 (sig = 0.005 < 0.05). (2). Work discipline has a partial effect on the performance of the state civil apparatus at the Barru Central Bureau of Statistics. Where the results obtained by work discipline have a t arithmetic value of 3.794 > t table 1.6973 and the significance level of t is less than 0.05 (sig = 0.000 < 0.05). (3). Compensation and work discipline simultaneously (simultaneously) affect the performance of the state civil apparatus at the Barru Central Bureau of Statistics. It can be seen that compensation and work discipline give a calculated Fvalue of 75.818 which is greater than the Ftable, which is 3.29 with a probability value of 0.000 which means it is below the significance value of 0.05.